2022
DOI: 10.1002/mgg3.2078
|View full text |Cite
|
Sign up to set email alerts
|

Novel biallelic mutations in TTC29 cause asthenoteratospermia and male infertility

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The genes involved in downregulation were identified as CFAP70 , TTC29 , CCDC40 , DNAAF4 , SYCE3 , STK36 , SPI1 , and EMX2 . These genes were found to be enriched in various pathways related to sex development, sperm growth, and sperm motility, such as organelle assembly, cilia movement, the development of the urogenital system, sperm production, and sperm deformity [ 47 , 48 ]. Significantly, various studies have shown that these genes contribute to reproductive development.…”
Section: Discussionmentioning
confidence: 99%
“…The genes involved in downregulation were identified as CFAP70 , TTC29 , CCDC40 , DNAAF4 , SYCE3 , STK36 , SPI1 , and EMX2 . These genes were found to be enriched in various pathways related to sex development, sperm growth, and sperm motility, such as organelle assembly, cilia movement, the development of the urogenital system, sperm production, and sperm deformity [ 47 , 48 ]. Significantly, various studies have shown that these genes contribute to reproductive development.…”
Section: Discussionmentioning
confidence: 99%